Metaheuristic-based optimal energy assessment of hybrid multi-effect evaporator with synergy of solar and wind energy sources - Smitarani Pati; Nandan Kumar Navin; Om Prakash Verma; Dwesh Kumar Singh; Tarun Kumar Sharma; Saurabh Agarwal; Santos Gracia Villar; Luis Alonso Dzul Lopez; Imran Ashraf (Heliyon)
This study emphasizes a multi-pronged approach to improving the energy efficiency of Multi-Effect Evaporator (MEE) in the paper industry. By incorporating traditional Energy-Saving Schemes (ESSs) and innovative renewable energy sources, the study demonstrates significant potential for reducing energy consumption and environmental impact, making it a decisive pathway for industrial sustainability. Key ESS strategies include Thermo-Vapor Compressors, Feed Preheaters, and Steam- and Feed-Split, which are employed to enhance Steam Economy (SE) to evaluate MEE efficiency. This integration results in a 67.93% enhancement in SE, reducing energy consumption significantly. Further, SE enhancement is achieved by integrating flash tanks that capture and reuse excess heat, which boosts SE by an additional 5.89%, leading to a total improvement of 73% without additional energy consumption. A significant innovation in the study is the integration of Linear Fresnel Reflectors (LFRs) based solar collectors and turbine-based wind energy sources to power the MEE and reduce reliance on conventional energy. This hybrid system decreases energy dependence by 62% for the base MEE and 34% for the hybrid MEE. The results are validated by comparing them with existing studies, confirming the effectiveness of the proposed method and offering significant energy and environment savings.